2020
DOI: 10.3390/pathogens9020127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Atranorin towards the Proliferation of Babesia and Theileria Parasites

Abstract: Atranorin (ATR), is a compound with multidirectional biological activity under different in vitro and in vivo conditions and it is effective as an antibacterial, antiviral, antiprotozoal and anti-inflammatory agent. In the current study, the in vitro as well as in vivo chemotherapeutic effect of ATR as well as its combined efficacy with the existing antibabesial drugs (diminazene aceturate (DA), atovaquone (AV) and clofazimine (CF)) were investigated on six species of piroplasm parasites. ATR suppressed B. bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…Moreover, Vathsala and Murthy [138] revealed the potent immunomodulatory and anti-plasmodial effect of garlic-artemether combination treatment. They reported that this combined therapy may have a potential role in reducing organ injury and protecting against Plasmodium species by affecting NO production, suggesting novel treatment options against malaria [138,139].…”
Section: Combination Therapy With Other Drugsmentioning
confidence: 99%
“…Moreover, Vathsala and Murthy [138] revealed the potent immunomodulatory and anti-plasmodial effect of garlic-artemether combination treatment. They reported that this combined therapy may have a potential role in reducing organ injury and protecting against Plasmodium species by affecting NO production, suggesting novel treatment options against malaria [138,139].…”
Section: Combination Therapy With Other Drugsmentioning
confidence: 99%
“…Moreover, quercetin is a potent competitive inhibitor of CYP3A4 (the enzyme responsible for drug degradation in the body) and was thus predicted to increase the serum concentrations of drugs (e.g., diltiazem) that are metabolized by this enzyme [107]. Therefore, research towards the optimum mechanism of action of natural compounds that prevents the adverse effects of plants and the development of new molecules with new pharmacological effects will continue [108][109][110].…”
Section: Quercetin-drug Interactionmentioning
confidence: 99%
“…In vitro combination treatment of MEVT and AELN with DMA and ATV Combination therapies of MEVT and AELN with DMA and ATV were tested using the fluorescence inhibition method as reported elsewhere [40,41]. Five selected dilutions (0.25 ×, 0.5 ×, 1 ×, 2 × and 4 × the IC 50 ) of the two herbal extracts with DMA and ATV were set up in three sets of duplicate wells and the parasite cultures were incubated for four consecutive days at 37°C humidifying incubator in 90% N 2 , 5% O 2 , and 5% CO 2 atmosphere without changing medium.…”
Section: Cytotoxicity Assay Of Mevt and Aeln On Normal Cellsmentioning
confidence: 99%